2018
DOI: 10.1111/jonm.12633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mentoring on professional values in model C clinical nurse leader graduates

Abstract: Formal mentoring relationships are powerful and should be used to promote professional values for model C clinical nurse leader graduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(31 reference statements)
0
9
1
Order By: Relevance
“…Unlike the quantitative Phase I and Phase II results reported in Gazaway et al (), this qualitative phase found that the participants showed no preference for type of mentoring relationship. Regardless of type of mentoring relationship, the Phase III participants identified with mentors who modelled excellence in nursing care and strove to emulate their clinical practice habits.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Unlike the quantitative Phase I and Phase II results reported in Gazaway et al (), this qualitative phase found that the participants showed no preference for type of mentoring relationship. Regardless of type of mentoring relationship, the Phase III participants identified with mentors who modelled excellence in nursing care and strove to emulate their clinical practice habits.…”
Section: Discussioncontrasting
confidence: 57%
“…The current study was part of a larger investigation that used a mixed methods design, which incorporated quantitative and qualitative techniques to collect data in three distinct phases. The detailed methodology and quantitative results from Phase I and Phase II were previously reported in Gazaway, Anderson, Schumacher, and Alichnie (). The current study is the qualitative Phase III, which was designed to delineate the impact of mentoring on professional socialization directly from the participants themselves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because professional development helps nurses to keep abreast of advances in nursing science (Berg Jansson & Engström, ; Jooste & Prinsloo, ), the implementation of formal mentoring for all clinical nurses is important to ensure that temporary nurses not only receive the same information and support that permanent nurses receive but also to develop temporary nurses to their full professional potential (Gazaway et al, ). Formal mentoring programmes expand trusted sources of information for permanent nurses (Fleig‐Palmer et al, ), allowing nurses to triangulate and critically evaluate a broader set of information.…”
Section: Discussionmentioning
confidence: 99%
“…Staffing is a common concern among international nurse managers because staffing not only affects the placement of nurses and the organisation of nursing teams (Cupit, Stout‐Aguilar, Cannon, & Norton, ; Holm‐Petersen, Østergaard, & Andersen, ; Jooste & Prinsloo, ; Maenhout & Vanhoucke, ; North et al, ), but it also influences how nurses relate to and support one another (Feather, Ebright, & Bakas, ; Gazaway, Anderson, Schumacher, & Alichnie, ; Gittell, ; Holland, Cooper, & Sheehan, ; McCabe & Sambrook, ). Despite the burgeoning interest in how managers communicate and support their nurses (Brunetto, Farr‐Wharton, & Shacklock, ; Hartung & Miller, ; Marx, ; Rouse & Al‐Maqbali, ; Timmins, ), the literature offers limited insights into how the proliferation of nurses' varied work arrangements affects the mentoring and support that nurses receive from their managers (Gan, ; Jones, ).…”
Section: Introductionmentioning
confidence: 99%